Effects of biochar and arbuscular mycorrhizal fungi on winter wheat growth and soil N2O emissions in different phosphorus environments - Hao, Zhuo; Dong, Zhijie; Han, Shuo; Zhang, Aiping (Frontiers in Plant Science, 2022)
Promoting crop growth and regulating denitrification process are two main ways to reduce soil N2O emissions in agricultural systems. However, how biochar and arbuscular mycorrhizal fungi (AMF) can regulate crop growth and denitrification in soils with different phosphorus (P) supplies to influence N2O emission remains largely unknown. Here, an eight-week greenhouse and one-year field experiments biochar and/or AMF (only in greenhouse experiment) additions under low and high P environments were conducted to characterize the effects on wheat (Triticum aestivum L.) growth and N2O emission. The addition of biochar and/or AMF had a negative effect on total root length of wheat under both low and high P supply. With low P supply, AMF addition decreased leaf Mn concentration (indicates carboxylate-releasing P-acquisition strategies), whereas biochar addition increased leaf Mn concentration, suggesting biochar and AMF addition regulated root morphological and physiological traits to capture P. Compared with low P supply, the high P significantly promoted wheat growth (by 16-34%), nutrient content (by 33-218%) and yield (by 33-41%), but suppressed soil N2O emissions (by 32-95%). Biochar and/or AMF addition exhibited either no or negative effects on wheat biomass and nutrient content in greenhouse, and biochar addition promoted wheat yield only under high P environment in field. However, biochar and/or AMF addition decreased soil N2O emissions by 24-93% and 32% in greenhouse and field experiments, respectively. This decrease was associated mainly with the diminished abundance of N2O-producing denitrifiers (nirK and nirS types, by 17-59%, respectively) and the increased abundance of N2O-consuming denitrifiers (nosZ type, by 35-65%), and also with the increased wheat nutrient content, yield and leaf Mn concentration. These findings suggest that strengthening the plant-soil-microbe interactions can mitigate soil N2O emissions via manipulating plant nutrient acquisition and soil denitrification.